The ability of the Reciproc R25 instrument to reach the full root canal working length without a glide path. (6th April 2013) - De‐Deus, G.; Arruda, T. E. P.; Souza, E. M.; Neves, A.; Magalhães, K.; Thuanne, E.; Fidel, R. A. S.
Abstract Aim To assess the frequency in which the Reciproc instrument reaches the full working length (FWL) of mandibular molar canals without a glide path. Methodology From a pool of mandibular molars, 253 root canals were classified as straight (G1) and, 249 root canals as moderately curved (G2) following Schneider's method. A R25 Reciproc instrument (VDW, Munich, Germany) was advanced in the canals without any previous glide path. All cases where Reciproc instruments reached the FWL were classified as 'Reaching the FWL' (RFWL). When the FWL was not reached by the R25, the root canals were classified as 'Not Reaching the FWL' (NRFWL). Pearson's χ2 test compared (i) the frequency distributions of root canals classified as RFWL and NRFWL for each group and (ii) the frequency distributions of NRFWL canals between the groups. Results In G1, 9 cases (3.56%) and in G2, 23 canals (9.34%) were classified as NRFWL. The difference between NRFWL and RFWL was significant in both groups (P = 0.00, χ 2 = 217.2 for G1; P = 0.00, χ 2 = 167.8 for G2). The frequency of NRFWL was significantly higher for G2 (P = 0.02, χ 2 = 5.452). Conclusion The R25 Reciproc instrument is able to reach the FWL of straight‐ and moderate‐curved mandibular molar canals without a glide path in a large proportion of cases.